Cranial reconstruction utilizing polymeric implants in two different designs: finite element investigation - Yomna H. Shash (BMC Musculoskeletal Disorders)
Abstract Introduction Impact loads applied to the human head can result in skull fractures or other injuries that require a craniectomy. The removed portion is replaced with biological or synthetic materials using cranioplasty surgery. Titanium has been the material of choice for cranial implants due to its superior properties and biocompatibility; however, its issues have prompted the search for substitute materials (e.g., polymers). The issues are related to the requirement for surface modification, casting, radiologic incompatibility and potential allergy risks. Recently, polymeric materials have been used in many fields as alternatives to titanium. Objective This research aims to conduct a finite element study to evaluate the skull reconstruction process by using PEEK and carbon fiber reinforced PEEK 30 and 60% in the production of cranial implants as alternatives to conventional titanium implants. Materials and methods A three-dimensional model of a defective skull was rehabilitated with a custom-made cranial implant. The implants were stimulated using two designs (plate and mesh), and different polymeric materials (PEEK and carbon fiber reinforced PEEK 30 and 60%) as titanium substitutes, under 2000 N impact force. Results The results illustrated that plate implants reduced the stresses on the skull and increased the stresses on brain tissues compared to mesh implants. Titanium, CFR-PEEK 30 & 60% implants (whether mesh or flat) were not prone to fracture, unlike mesh PEEK implants. In addition, CFR-PEEK 60% implants produced the lowest values of stress, strain, and total deformation on the skull and brain compared to titanium implants, unlike PEEK implants. By using the titanium plate implant, the peak tensile and compressive stresses on the skull were 24.99 and 25.88 MPa, respectively. These stresses decreased to 21.6 and 24.24 MPa when using CFR-PEEK 60%, increased to 26.07 and 28.99 MPa with CFR-PEEK 30%, and significantly increased to 41.68 and 87.61 MPa with PEEK. When the titanium mesh implant was used, the peak tensile and compressive stresses on the skull were 29.83 and 33.86 MPa. With CFR-PEEK 60%, these stresses decreased to 27.77 and 30.57 MPa, and with CFR-PEEK 30% and PEEK, the stresses increased to 34.04 and 38.43 MPa, and 44.65 and 125.67 MPa, respectively. For the brain, using the titanium plate implant resulted in peak tensile and compressive stresses of 14.9 and 16.6 Pa. These stresses decreased to 13.7 and 15.2 Pa with CFR-PEEK 60%, and increased to 16.3 and 18.1 Pa, and 73.5 and 80 Pa, with CFR-PEEK 30% and PEEK, respectively. With the titanium mesh implant, the peak tensile and compressive stresses were 12.3 and 13.5 Pa. Using CFR-PEEK 60%, these stresses decreased to 11.2 and 12.4 Pa on the brain, and increased with CFR-PEEK 30% and PEEK to 14.1 and 15.5 Pa, and 53.7 and 62 Pa, respectively. Additionally, the contact area between the PEEK implant (whether mesh or plate design) and the left parietal bone of the skull was expected to be damaged due to excessive strains. Importantly, all implants tested did not exceed permissible limits for tensile and compressive stresses and strains on the brain. Conclusion It was concluded that carbon fiber-reinforced PEEK implants, with 30% and 60% reinforcements, can be used as alternatives to titanium for cranial reconstruction. The addition of carbon fibers to the PEEK matrix in these percentages enhances the mechanical, chemical, and thermal properties of the implants. Additionally, these composites are characterized by their low weight, biocompatibility, lack of clinical issues, and ease of fabrication. They can also help preserve the skull, protect the brain, and are not susceptible to damage. Clinical significance Overcoming the drawbacks of titanium cranial implants and increasing the effectiveness of the cranioplasty process by utilizing PEEK and carbon fiber reinforced PEEK materials in the reconstruction of the damaged portion of skull.